Low-Temperature-Induced Expression of Rice Ureidoglycolate Amidohydrolase is Mediated by a C-Repeat/Dehydration-Responsive Element that Specifically Interacts with Rice C-Repeat-Binding Factor 3 - Li, Juan (Front Plant Sci, 2015)
Nitrogen recycling and redistribution are important for the environmental stress response of plants. In non-nitrogen-fixing plants, ureide metabolism is crucial to nitrogen recycling from organic sources. Various studies have suggested that the rate-limiting components of ureide metabolism respond to environmental stresses. However, the underlying regulation mechanism is not well understood. In this report, rice ureidoglycolate amidohydrolase (OsUAH), which is a recently identified enzyme catalyzing the final step of ureide degradation, was identified as low-temperature- (LT) but not abscisic acid- (ABA) regulated. To elucidate the LT regulatory mechanism at the transcriptional level, we isolated and characterized the promoter region of OsUAH (P(OsUAH)). Series deletions revealed that a minimal region between –522 and –420 relative to the transcriptional start site was sufficient for the cold induction of P(OsUAH). Detailed analyses of this 103-bp fragment indicated that a C-repeat/dehydration-responsive (CRT/DRE) element localized at position –434 was essential for LT-responsive expression. A rice C-repeat-binding factors/DRE-binding proteins 1 (CBFs/DREB1s) subfamily member, OsCBF3, was screened to specifically bind to the CRT/DRE element in the minimal region both in yeast one-hybrid assays and in in vitro gel-shift analysis. Moreover, the promoter could be exclusively trans-activated by the interaction between the CRT/DRE element and OsCBF3 in vivo. These findings may help to elucidate the regulation mechanism of stress-responsive ureide metabolism genes and provide an example of the member-specific manipulation of the CBF/DREB1 subfamily.